Sporsøgeren Carlo Ginzburg - Bay, Ole (Religionsvidenskabeligt Tidsskrift, 1992)
The article gives an introduction to the wotk of the Italian historian Carlo Ginzburg, known worldwide specially for the books The Cheese and the Worms, The Night Battles and Ecstasies. Deciphering hte Witches’ Sabbath. Working on source material from the archives of the Inquisition, Ginzburg has tried to recover the authentic popular beliefs from the distortions they have been subjected to in the official interrogations of the Inquisition. A main theme in his research has been a continuous effort to explain the phenomenon benandanti, those "good wanderers" who fought nightly battles against the witches in sixteenth century Friuli in norther Italy - according to what the peasants told the Inquisition. In his latest book, on the origens of the witches’ sabbath, Ginzburg sees the phenomenon in a tradition of Euro-Asiatic shamanism. That has been much debated, and although Ginzburg’s theories only partly explain the with-persecutions of early nmodern Europe, they certainly throw new light on popular beliefs, and therefore they can not be ignored.